Bagaimana Live Streaming Selling, Review Product, Discount dan Sosial Media Marketing Mempengaruhi Minat Beli Lipstik Maybelline di Shopee: Studi pada Mahasiswa di Universitas di Purwokerto - Resti Meilani; Herni justiana Astuti; Wida Purwidianti; Totok Haryanto (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
This study aims to analyze the influence of Live streaming selling, Product Reviews, Discounts, and Social Media Marketing on the purchase intention of Maybelline lipstick at the official Shopee store. The study employed a quantitative approach using a survey method. Data were collected through questionnaires distributed to 121 active students in Purwokerto, selected using purposive sampling. Data analysis was conducted using SPSS version 25 through multiple linear regression. The t-test results show that Live streaming selling, Product Reviews, and Discounts have a significant effect on purchase intention, while Social Media Marketing does not. The Adjusted R Square value of 0.638 indicates that 63.8% of the variation in purchase intention can be explained by these four variables. These findings suggest that direct interaction through Live streaming selling and the trust formed from Product Reviews play an important role in influencing consumer purchase intention on Shopee e-commerce